Does women's empowerment through policy intervention reduce food insecurity in South Africa?. Issue 1 (2nd January 2019) - Bahta, Yonas T.; Owusu-Sekyere, Enoch; Tlalang, Boipelo
ABSTRACT: This article determines the extent to which the food insecurity status of women in South Africa can be reduced by participating in gardening around the homestead, using survey data from 207 women farmers. A household food insecurity average score index and an empirical model that accounts for observed and unobserved factors contributing to food insecurity were employed. The findings reveal that participating in the programme worked to reduce the food insecurity of women significantly, and also show other policy factors that need to be taken into consideration to reduce food insecurity. We recommend that policy interventions towards promoting high participation by women are a sustainable strategy to address food insecurity and to achieve the 2030 agenda targeting an end to poverty and hunger.